2022
DOI: 10.3390/land11020248
|View full text |Cite
|
Sign up to set email alerts
|

Horizon Scan of Transboundary Concerns Impacting Snow Leopard Landscapes in Asia

Abstract: The high-altitude region of Asia is prone to natural resource degradation caused by a variety of natural and anthropogenic factors that also threaten the habitat of critical top predator species, the snow leopard (Panthera uncia). The snow leopard’s landscape encompasses parts of the twelve Asian countries and is dominated by pastoral societies within arid mountainous terrain. However, no investigation has assessed the vulnerability and pathways towards long-term sustainability on the global snow leopard lands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 192 publications
0
9
0
Order By: Relevance
“…A study in the Himalayas revealed that vulnerability has increased due to deforestation, crop encroachment, and grazing [106]. Similar trends have been observed worldwide because population growth and land use/cover changes enhance the vulnerability of the inhabitants [107][108][109]. Prior studies have shown that the vulnerability of the human population is showing an increasing trend to natural hazards around the world [110,111].…”
Section: Drivers Of Vulnerability In the Himalayasmentioning
confidence: 78%
“…A study in the Himalayas revealed that vulnerability has increased due to deforestation, crop encroachment, and grazing [106]. Similar trends have been observed worldwide because population growth and land use/cover changes enhance the vulnerability of the inhabitants [107][108][109]. Prior studies have shown that the vulnerability of the human population is showing an increasing trend to natural hazards around the world [110,111].…”
Section: Drivers Of Vulnerability In the Himalayasmentioning
confidence: 78%
“…Having cognizance of this, land‐use changes due to neo‐liberal extractive forms of development, along with climate‐related uncertainties, threaten pastoral communities living in close proximity of elusive wildlife across regions of High Asia, including Changthang (Mishra et al, 2022; Sultan et al, 2022). Therein, we believe that conserving pastoralism as a form of livelihood is not only ecologically and culturally beneficial, but also, perhaps most compellingly, an issue of rights.…”
Section: Authors' Positionalitymentioning
confidence: 99%
“…Meeting the needs of the future through landscape-scale approaches will be important to maintain the integrity of species and systems that span multiple political and physical geographies. Sultan et al [15] have found the protection of the globally endangered snow leopard requires transboundary agreements and cooperation amongst the 12 countries that encompass the leopard's range. Similarly, a review of the European Union's agricultural biodiversity conservation policy reveals a gap in the potential to address critical issues because it is not including adequate landscape-scale design in its post-2023 plan [16].…”
Section: Landscape-scale Approachesmentioning
confidence: 99%